Droit d’auteur et restauration des œuvres à caractère technologique - Anne-Laure Moya-Plana (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Reconciling the rules of copyright with the principles of restoration and, more specifically, articulating the rights of the artist and of his successors with those of the museum that acquired the work of art, is a delicate endeavor. The goal is to establish, as soon as the work of art is acquired by the museum, a dialogue between the artist and the curator or the restorer so as to anticipate any conflict and fix the outlines of the future restoration in a contract.